PENGEMBANGAN MEDIA KARTU BERGAMBAR BERBANTUAN CANVA DALAM PEMBELAJARAN BAHASA INDONESIA UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS II SEKOLAH DASAR - Annisa, Nur; Muhammadi; Adrias; Shilfia Iraqi, Hana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the low initial reading skills of second-grade elementary school students. The problem was indicated by students' difficulties in recognizing letters, syllables, words, and simple sentences, while the learning media used by teachers had not optimally improved students' early reading abilities. This study aimed to develop Canva-assisted picture card media for Indonesian language learning on Chapter V, Being Friends in Diversity, and to examine its validity, practicality, and effectiveness. This study employed a Research and Development (R&D) approach using the ADDIE model, consisting of the Analysis, Design, Development, Implementation, and Evaluation stages. Data were collected through validation sheets completed by material, media, and language experts, teacher and student response questionnaires, and pretest-posttest assessments of beginning reading skills. The results showed that the developed media achieved an average validity score of 89.03%, categorized as very valid. The media was also considered very practical, with teacher and student response scores of 95.31% and 95.95%, respectively. Furthermore, the media proved to be effective in improving students' beginning reading skills, as indicated by N-Gain scores of 78.81% at SD N 07 Binuang Kampung Dalam and 72.99% at SD N 03 Binuang Kampung Dalam, both categorized as effective. Therefore, the Canva-assisted picture card media is feasible and effective for improving beginning reading skills in Grade II Indonesian language learning at elementary schools.